Development of E-Modules Based on Problem-Based Learning to Increase the Creativity of Grade 2 Elementary School Students in Mathematics Subjects - Marina Amini; Zelhendri Zen; Abna Hidayati; Rayendra (Postgraduate, University of Mataram, 2025)
The urgency of this study stems from the lack of interactive and contextual learning media in early-grade mathematics, which limits students’ creativity. This research aimed to develop an electronic module based on Problem-Based Learning to enhance the creative thinking skills of second-grade elementary students, particularly in learning simple fractions. Employing a research and development approach using the Plomp model, the study consisted of three phases: preliminary research, prototyping, and assessment. Data were collected through expert validation, questionnaires, and student performance assessments, then analyzed using descriptive quantitative techniques. The results showed that the developed e-module was valid based on expert judgment (average validity score > 0.90), practical according to teacher and student responses (average practicality > 85%), and effective in improving creativity, as evidenced by increased scores in fluency, flexibility, and originality (mean score 80.44%). The findings indicate that integrating Problem-Based Learning into digital modules can significantly support the development of students' creativity and engagement in mathematics. This innovation offers practical implications for curriculum-aligned learning media and supports the development of 21st-century skills. Further research is recommended to explore broader applications and incorporate adaptive digital features.